The acoustic reactance of radiation of a planar annular membrane for axially-symmetric free vibrations - RDZANEK, W. J.; RDZANEK, W. P. Jr. (Archives of Acoustics, 1999)
The imaginary part of the acoustic impedance of radiation of a planar, annular membrane is analyzed. Axially-symmetric free vibrations, sinusoidally varying in time, are considered. An annular membrane is placed in a planar, rigid baffle and radiates an acoustic wave into a loss-less, homogeneous, gaseous medium. The reactance of radiation is obtained in an elementary form for high frequencies of radiated waves.